Agronomic and Economic Effect of Irrigation Rate in Cotton. Issue 1 (12th June 2015) - Lamb, Marshall C.; Sorensen, Ronald B.; Nuti, Russell C.; Butts, Christopher L.
Abstract : Although the Southeast United States receives an average annual precipitation of 51.2 inches, cotton ( Gossypium hirsutum L.) yield is often limited by erratic seasonal distributions. The objective of this research was to determine the effects of irrigation level on lint yield, net return over variable cost (NR), water use efficiency (WUE), water use efficiency to irrigation (WUEi ), and returns to water use efficiency to irrigation (RWUEi ) for cotton. Studies were conducted from 2001 to 2012 in Shellman, Georgia (84° 36′ W, 30° 44′ N) on a Greenville fine sandy loam (fine, kaolinitic, thermic Rhodic Kandiudults). Irrigation levels of 100, 66, 33%, and a non‐irrigated control were examined with the 100% level following the recommendations of Irrigator Pro for Cotton. The other water levels were applied at the same time and in proportion to the 100% level. The 100% irrigation level increased lint yield compared to non‐irrigated yield in 10 of the 12 years and increased NR eight of the 12 years. Water use efficiency, WUEi, and RWUEi responded differently across irrigation levels depending on precipitation grouping. The highest WUE and WUEi occurred in the 66% irrigation level during below average rainfall years at 57.06 and 92.68 lb ac −1 in −1, respectively. The highest RWUEi also occurred in the 66% rate during the below average rainfall years at $58.28 ac −1 in −1 . The results showed that adequate irrigation resources are critical to cotton production over the long term and especially in years of moderate to less than average precipitation.